Sustainable Intensification of Smallholder Maize Production in Northern Ghana: The Case of Basal Fertilizer Timing. - Rahman, Nurudeen Abdul; Kizito, Fred; Kotu, Bekele; Hoeschle-Zeledon, Irmgard; Bekunda, Mateete A. (CGIAR System Organization, 2024)
Assessment of sustainable intensification of agricultural technologies is evolving with limited information in literature. A 2-year (2019-2020) on-farm study was conducted to assess the sustainability of basal NPK fertilizer application timing in smallholder maize cropping system in northern Ghana. The experimental design was RCBD with sixty-seven farmers as replicates. The treatments were application of two types of NPK fertilizer (Blend and Compound) at: i. planting, ii. 2 weeks after planting (2WAP; conventional practice) and iii. At planting+2WAP. We used Sustainable Intensification Assessment Framework (SIAF) to assess the sustainability of the above treatments. The SIAF assess the sustainability of agricultural technologies based on five domains (productivity, economic, environment, human and social). We conducted the assessment in three steps: 1) Measuring selected indicators from the five SIAF domains useful to answering research question, 2) Conversion of measured values of selected indicators into scores using a scale of 0-1 and 3) Aggregation of scores to calculate sustainability index (SI) using geometric rules considering each SIAF domain as an edge of a pentagon. Specific indicators by domain measured in this study were: grain yield, nitrogen (N) use efficiency and nutrient efficiency ratio (productivity), labor requirement, profitability and return on investment (economic), partial N budget, and ammonia flux emission (environment), calorie production (human) and technology rating by gender (social). Applying both type of NPK fertilizers to maize at planting recorded higher productivity (62-67%), economic (149-154%), environment (15%), human (73-98%) and social (nine-fold) domains relative to the other treatments. The SI for applying both fertilizer types at planting of maize increased by two-four-fold compared with the other treatments. We recommend applying basal NPK fertilizer to maize at planting will enhance sustainability of smallholder maize production in northern Ghana and similar agro-ecologies through its effect on productivity, income, environmental pollution, food security and gender equity.